Air-blast loading on empty metallic beverage can used as sacrificial cladding: Experimental, analytical and numerical study. (1st February 2020) - Ousji, H.; Belkassem, B.; Pyl, L.; Vantomme, J.
Highlights: Design of an adequate experimental set-up to study the dynamic crush of a thin-walled tube, in particular, an empty metallic beverage can axially loaded. Comparison between the effect of a low impact velocity and a dynamic load, on the deformation pattern, the mean crush load and the absorption capacity. Study of the effect of the entrapped gases inside the MBC structure on the prediction of the mean crush load. Abstract: The aim of this work is to study the response of a sacrificial cladding using metallic beverage can (MBC) as crushable core. A single MBC axially crushed is considered. An adequate experimental set-up is developed to examine the collapse pattern, the mean crush load and the absorption capacity of a single MBC under a blast load. A comparison with low velocity impact is discussed. The effect of both the entrapped gases inside the MBC and the crush velocity are investigated through analytical and numerical studies. A clear loading rate dependency of the mean crush load is observed. It varies from 0.94 kN to 1.35 kN by increasing the front plate velocity from 17 m/s (FP3) to 44 m/s (FP1). The effect of the entrapped gases inside the MBC structure increases the mean crush load, and, then, the transmitted load to the main structure. In addition to the dynamic material properties, the entrapped gases are considered for an accurate prediction of the mean crush load. Good correlation with the experimental results is observed.